Iowa Birdline update, February 15, 1993 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1993)
Email for the Iowa Birdline update for February 15, 1993. Highlights of the update include sightings of two Chinese Thrushes, an interesting exotic seen daily in an Ottumwa backyard for several months. Also included are handwritten notes for the next week's update with sightings of three Golden-crowned Kinglets and two Trumpeter Swans. Epson - sheet feed/flatbed